The prevalence and factors associated with low back pain in Physiotherapy students at the University of the Witwatersrand - Burger, Salmina Magdalena (My University, 2013)
The research reported in this dissertation centered around the prevalence and factors associated with low back pain (LBP) among the undergraduate physiotherapy students at the University of the Witwatersrand. Physiotherapy students are prone to LBP due to a flexion posture while studying, lifting patients and working. After pathology, muscle activity is influenced, affecting optimal function of the spine. Preventative strategies can minimise recurrences of LBP. Physiotherapy students enrolled for 2010 at the University of the Witwatersrand participated in a cross-sectional prevalence study. A questionnaire, multi-stage fitness test and physical assessment were completed. Statistical analysis was done with univariate analysis for associations with LBP. The study revealed that the lifetime LBP prevalence was 35.6% among all four physiotherapy year groups. The prevalence increased from first year to third year but unexpectedly decreased in the fourth year group. Significant associations with LBP were posterior-anterior mobilisations on L4 (p=0.003) and L5 (p≤0.001) centrally, left lumbar multifidus (LM) cross-sectional area (p=0.02), right obliquus internus abdominis (p=0.02) and transversus abdominis (TrA) thickness at rest (p=0.03), both TrA during contraction, left (p=0.02) and right (p=0.01), as well as the pull of the TrA during contraction on the left (p=0.03). The present work is the first study to show measurements with ultrasound imaging of LM and TrA on physiotherapy students. The prevalence of LBP might be reduced if students are more aware of LBP and consequential muscle imbalances that might perpetuate the problem. The dissertation concludes with a discussion of future research avenues. It is suggested that an intervention to make students aware of LBP and risk assessments in South Africa will help to identify and address hazards in the workplace.
Keywords: Low Back Pain